Water dynamics and ground water quality assessment in an oil palm ecosystem - Lubis, Muhammad Edwin Syahputra (2016)
Oil palm crops have been estimated to use a lot of water for their growth and production. Hence, oil palm can cause a decline in the soil water table. In addition, oil palm also requires the use of fertilizers to maximize its growth and crop production, and this has led to detrimental effects on the ground water quality. Leaching causes a loss of nutrients as they are washed further downward into the soil apart from causing ground water pollution, eventually. Ground water contamination can cause serious problems to ground water as it is the main water source used by most people to meet their drinking water needs. Furthermore, there is still very little information about the sources of water uptake by oil palm although the information is important for water management system at oil palm plantations. Hence, there is a need to evaluate water use and water quality at oil palm plantations. This study was undertaken with the following objectives: i. To evaluate the impact of climatic factors on water table of an oil palm plantation and its surrounding region; ii. To investigate the impact of oil palm fertilization on ground water quality; iii. To identify water sources of oil palm; and iv. To evaluate a water table model for an oil palm plantation. The study on the dynamics of water table level at an oil palm plantation and its surrounding region was carried out by conducting a daily monitoring on water table level at Kabun – Aliantan (N: 0002.925’E: 100049.977’) watershed area in Tandun, Riau, Indonesia, from 2009 until 2011. Data analyses that were carried out included the correlation analysis on the water table level at each well point location with several climate elements in the same time period, and the correlation analysis on the changes on water table levels between the oil palm area and other locations during the same period. Besides, the study was also carried out to analyze the water system at a mature oil palm area, where an observation plot was built to measure the water balance in the area. The variables used to measure changes at the observation plot were precipitation, soil surface, evaporation, and runoff. Based on these variables, water infiltration was then determined.The results showed that the height of water table level in the oil palm plantation area is related to elements of water balance which include rainfall, interception, evapotranspiration, and surface runoff water. Data show that water table level that declined in the dry season period increased again during the rainy season, indicating that the decline in water table level was not permanent. Water table levels in the area surrounding the oil palm plantation also fluctuated based on the conditions of rainfall. The decline in water table level in the area surrounding the oil palm plantation did not correlate with the oil palm crop itself. However, the condition of the water table at any location in the oil palm plantation areas shows that there is a relationship between one location to another. Evaluations made based on the water table dynamics model fitted rather well the results of direct measurements, with coefficient of determination (R²) of 0.8138 or 81.38 %. The value of Root Mean Square Error (RMSE) between the model and direct measurement was 27.33 mm while the correlation coefficient between the model and direct measurement was 0.90. There is a relationship between water table level and oil palm productivity. Water table level at lag time of 8-9 months and 33-35 months before harvest affects oil palm productivity. Oil palm plantations need fertilizers for optimum growth and production. However, excessive use of fertilizers can lead to ground water contamination. Due to this, a study on the quality of ground water in an oil palm ecosystem had been conducted. It involved monitoring of 9-point monitor wells and measurements of runoff. The parameters analyzed in the water samples were pH, nitrate-N (NO3-N), nitrite-N (NO2- N), ammonium-N (NH4-N), phosphate (P), potassium (K), calcium (Ca), and magnesium (Mg). The findings of the study showed that the concentrations of pH, Nitrate-N (NO3 -), Nitrite-N (NO2 -), Ammonium-N (NH4 +), Phosphate (P), Potassium (K+), Calcium (Ca), and Magnesium (Mg) at the oil palm plantation did not exceed the contamination level for safe drinking water set by WHO. In general, the increased concentrations of pH, Nitrate-N (NO3 -), Nitrite-N (NO2 -), Ammonium-N (NH4 +), Phosphate (P), Potassium (K), Calcium (Ca), Magnesium (Mg) that occured after fertilizer application eventually decreased with time. This study clarified that fertilizer treatments in the oil palm plantation did not reduce the quality of ground water although data showed that the value of Ammonium-N (NH4 +) was high in the housing complex and exceeded the safe drinking water limit set by WHO. The study also aimed to determine the current water source absorbed by the roots of oil palm by using the deuterium (δD) and oxygen isotope (δ18 O) method. The signatures of deuterium and oxygen isotope in total rainfall, throughfall, runoff, measurement at 5 soil depths (20 cm, 50 cm, 100 cm, 150 cm, and 200 cm), and in the stems of oil palm. The results showed that the values of deuterium and oxygen isotope varied significantly. Based on the Least Significant Difference (LSD) test, no significant difference was found in the deuterium and oxygen isotope in the stem water samples and other samples. This experiment showed that oil palm absorbs a mixture of soil water of ground water, soil water, and precipitation from several soil layers. Similar isotope signatures were also obtained from water samples taken at the depth of 0-50 cm and in the stem water. This result is in accordance with the oil palm root system, i.e. the quarternary roots (0-50 cm) is the most active root of oil palm that absorbs nutrients, water, and oxygen. This indicates that oil palm possibly absorbs water more dominantly from the depth of 0-50 cm.